The effect of electrical current on premature failures and microstructural degradation in bearing steel. (April 2021) - Gould, Benjamin; Demas, Nicholas; Erck, Robert; Lorenzo-Martin, Maria Cinta; Ajayi, Oyelayo; Greco, Aaron
Highlights: A custom testing methodology was developed to apply electrical current to a rolling/sliding contact. The level of applied current, and lubricant chemistry were varied. Tests performed at above 75 mA showed a significant decrease in macro-pitting fatigue life. Lubricant chemistry had a drastic effect on time to failure, suggesting that electrotribochemistry plays a role in failure. Abstract: Premature failures associated with microstructural degradation, i.e. white etching cracks (WECS), are becoming commonplace as applications are requiring tribological components to operate under extreme conditions. Although the specific drivers of WECs are still debated, the failures are often found in applications where cyclic loading is combined with added energy from stressors such as slip, impacts, or stray current. The aim of the current work is to elucidate effect that variable current has on premature failure. Numerous commercially available lubricants were tested, and both lubricant base oil type and additive package were found to have an effect on WEC failure time.